Paid childcare leave, fertility, and female labor supply in South Korea - Kim, Kyeongkuk,Lee, Sang-hyop,Halliday, Timothy (IZA - Institute of Labor Economics, 2022)
We consider the effects of a paid childcare leave subsidy on maternal behavior in South Korea using a difference-in-difference design and a fertility survey with information on conception, contraception, and labor supply arrangements. Childcare subsidies increased conception and decreased contraception. The arc elasticities of the responses of conception and contraception to the childcare subsidy are 0.65 and -0.10, respectively. However, we do not find effects on employment arrangements. In a country with the lowest total fertility rate in the world and that often performs middling in rankings of gender inequality, we conclude that paid childcare leave for working women confers some positive benefits.
10419/263439
Keywords: Graue Literatur; childcare leave; fertility; labor supply; Korea